2016
DOI: 10.3390/molecules21081094
|View full text |Cite
|
Sign up to set email alerts
|

Compositions, Formation Mechanism, and Neuroprotective Effect of Compound Precipitation from the Traditional Chinese Prescription Huang-Lian-Jie-Du-Tang

Abstract: Abstract:Compounds in the form of precipitation (CFP) are universally formed during the decocting of Chinese prescriptions, such as Huang-Lian-Jie-Du-Tang (HLJDT). The formation rate of HLJDT CFP even reached 2.63% ± 0.20%. The identification by liquid chromatography mass spectrometry (LC-MS n ) proved that the main chemical substances of HLJDT CFP are baicalin and berberine, which is coincident with the theory that the CFP might derive from interaction between acidic and basic compounds. To investigate the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 22 publications
5
12
0
Order By: Relevance
“…As shown in Table 2 , five constituents were characterized and determined based on their retention behaviors and MS data. The result showed that the main ingredients of SB-CC CFP were baicalin (2) and berberine (4), which was consistent with the results of previous studies on the chemical substances of HLJDT CFP [ 15 ], proving the interactions between Scutellaria baicalensis and Coptis chinensis to be the main source of HLJDT CFP.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…As shown in Table 2 , five constituents were characterized and determined based on their retention behaviors and MS data. The result showed that the main ingredients of SB-CC CFP were baicalin (2) and berberine (4), which was consistent with the results of previous studies on the chemical substances of HLJDT CFP [ 15 ], proving the interactions between Scutellaria baicalensis and Coptis chinensis to be the main source of HLJDT CFP.…”
Section: Resultssupporting
confidence: 89%
“…However, as the absolute value of Δ G was not very high, this reaction was not very violent. As shown in Table 4 , the estimated stoichiometric ratio (n) was 1.002, indicating the binding ratio of baicalin and berberine was 1:1, which conformed to the result of baicalin-berberine complex 1 H-NMR and 13 C-NMR test [ 15 ]. Δ H = −371.6 kJ/mol, −TΔ S = 336.027 kJ/mol, which indicated that most of the binding energy was enthalpy, as the entropy change (Δ S ) of binding contributed unfavorably [ 16 , 24 ].…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…This result might provide an idea to explain the combination of Scutellaria baicalensis Georgi and Coptis chinensis Franch rhizome to treat diarrhea by TCM. Finally, BA-BBR NPs showed better therapeutic effect on IBS-D than BA/BBR mixture, suggesting that the synergistic effect of BBR and BA is achieved due to the formation of self-assemblies rather than the simple mixing, which is consistent with the results of our research in vitro ( Zhang et al, 2016 ; Wang et al, 2017 ; Huang et al, 2020 ).…”
Section: Discussionsupporting
confidence: 90%